Antidiarrhoeal evaluation of rhizomes of Cryptocoryne spiralis Fisch. ex Wydler: Antimotility and antisecretory effects - Prasad S.K.; Laloo D.; Kumar R.; Sahu A.N.; Hemalatha S. (My University, 2025)
The antidiarrhoeal activity of Cryptocoryne spiralis rhizomes extract (250, 500, 750 mg/kg, po) was evaluated using faecal excretion, castor oil-induced diarrhoea, small intestinal transit, intestinal fluid accumulation, gastric emptying and PGE2 induced enteropooling models in rats. In addition, various biochemical estimations, histopathological studies and antibacterial evaluations on strains responsible for diarrhoea were also performed. The results illustrated a significant reduction in normal faecal output rate after 5th and 7th h of treatment, while castor oil-induced diarrhoea model depicted a protection of 55.44% at same dose level from diarrhoea. The other models except, gastric emptying test demonstrated more pronounced effect at same dose level. A significant inhibition in nitric oxide, increase in carbohydrates, protein, DNA, Na+ and K+ level with minimum degeneration of colonic fibrous tissues and potent antibacterial activity were also observed. The antidiarrhoeal potential of C. spiralis may be as a result of antimotility and antisecretory type effect mediated through nitric oxide pathway.